2013
DOI: 10.1186/1750-1326-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Sustained, neuron-specific IKK/NF-κB activation generates a selective neuroinflammatory response promoting local neurodegeneration with aging

Abstract: BackgroundIncreasing evidence indicates that neuroinflammation is a critical factor contributing to the progression of various neurodegenerative diseases. The IKK/NF-κB signalling system is a central regulator of inflammation, but it also affects neuronal survival and differentiation. A complex interplay between different CNS resident cells and infiltrating immune cells, which produce and respond to various inflammatory mediators, determines whether neuroinflammation is beneficial or detrimental. The IKK/NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 78 publications
4
48
0
Order By: Relevance
“…demonstrated that activated IKK-β/NF-κB-induced neuroinflammation promotes neurodegeneration during aging. In this study, we investigated whether Aβ 1-42 increased the expression of IKK-β/NF-κB, which can trigger other inflammatory mediators66. Vanillic acid treatment reversed the Aβ 1-42 -induced elevated expression of IKK-β/NF-κB and reduced the activity of IKKβ/NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that activated IKK-β/NF-κB-induced neuroinflammation promotes neurodegeneration during aging. In this study, we investigated whether Aβ 1-42 increased the expression of IKK-β/NF-κB, which can trigger other inflammatory mediators66. Vanillic acid treatment reversed the Aβ 1-42 -induced elevated expression of IKK-β/NF-κB and reduced the activity of IKKβ/NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…80 However, aberrant activation of the IKK/NF-κB axis has been linked to selective neuroinflammation and apoptosis independent of neurodegeneraion. 81 In the context of metabolic damage, it has been shown that inhibition of the IKK/NF-κB axis using the terpenoid (Rb1) reduces inflammation and leptin resistance in the hypothalamus. 82 Furthermore, it has also been shown that lipotoxicity activates the proinflammatory axis IKKβ-NF-κB in the hypothalamus, promoting the generation of insulin resistance.…”
Section: The Tlr-ikkβ-nf-κb Pathway In the Development Of Type 2 Diabmentioning
confidence: 99%
“…Studies of the central actions of IKKβ have concentrated on neurodegenerative or metabolic disorders, but did not involve ethanol exposure (Zhang et al, 2008; Maqbool et al, 2013). Other studies have shown that IKKβ gene expression was altered in postmortem prefrontal cortex (PFC) from alcoholic individuals (Flatscher-Bader et al, 2005) and mouse PFC following ethanol exposure and in selectively bred animals predisposed to drink alcohol (Mulligan et al, 2006; Osterndorff-Kahanek et al, 2015).…”
Section: Introductionmentioning
confidence: 99%